2018
DOI: 10.1111/jen.12502
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cry3Bb1 resistance and intoxication in western corn rootworm by RNA sequencing

Abstract: The western corn rootworm (WCR) Diabrotica virgifera virgifera LeConte is a major pest of corn that has evolved resistance to transgenic maize that produces insecticidal Cry toxins. The specific mode of action of Cry3Bb1 and mechanism of resistance in WCR are unknown. This study compared gene expression between Cry3Bb1-susceptible and Cry3Bb1-resistant WCR neonates, in the presence and absence of Cry3Bb1. RNA-Seq data were analyzed to identify differentially expressed transcripts between strains of WCR, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 104 publications
3
14
1
Order By: Relevance
“…Contreras et al (2013) found a type of cadherinlike Cry3Aa receptor in Tribolium Castanea (Coleoptera: Tenebrionidae) and confirmed through gene silencing that the cadherin-like protein was a representative Cry receptor. In this study, one CAD gene was downregulated in A vs. CK, which was similar to the response of western corn root worm to Cry3Bb1 (Rault et al, 2018), which may be related to the pore formation model. Both APN and ALP are glycosylphosphatidylinositol (GPI)-anchored proteins, which play a role in the process of membrane insertion and pore formation.…”
Section: Transcriptional Response Of a Glabripennis Larvae To Bt Toxinsupporting
confidence: 68%
“…Contreras et al (2013) found a type of cadherinlike Cry3Aa receptor in Tribolium Castanea (Coleoptera: Tenebrionidae) and confirmed through gene silencing that the cadherin-like protein was a representative Cry receptor. In this study, one CAD gene was downregulated in A vs. CK, which was similar to the response of western corn root worm to Cry3Bb1 (Rault et al, 2018), which may be related to the pore formation model. Both APN and ALP are glycosylphosphatidylinositol (GPI)-anchored proteins, which play a role in the process of membrane insertion and pore formation.…”
Section: Transcriptional Response Of a Glabripennis Larvae To Bt Toxinsupporting
confidence: 68%
“…Several protein families including the ATP-binding cassette (ABC) transporters, cadherin, aminopeptidase N (APN), and alkaline phosphatase (ALP) have been identified as receptors of Cry toxins in Lepidoptera where more extensive studies were performed 36,37 . Interestingly, some of these protein classes are differentially expressed in Cry3-resistant WCR or WCR treated with Bt toxins (Cry34/35Ab1, Cry3Bb1, or eCry3.1Ab) 35,38,39 but have yet to be validated as functional receptors.…”
Section: Western Corn Rootworm (Wcr) Diabrotica Virgifera Virgifera mentioning
confidence: 99%
“… Ingber and Gassmann (2015 ) found differences between Hopkinton and Cresco in the life-history traits displaying fitness costs, the inheritance of resistance, and the magnitude of resistance, and it also appears that these strains differ in the extent to which ecological conditions may affect the manifestation of fitness costs. Furthermore, a recent study examining gene expression showed that Cry3Bb1 does not elicit a stress response in Hopkinton, further demonstrating that resistance in this strain is robust ( Rault et al 2018 ). This may also partially explain why Cresco was affected by differing larval densities, while Hopkinton was not.…”
Section: Discussionmentioning
confidence: 97%